Evaluating diagnostic and management agreement between physiotherapists and ear, nose and throat specialist in a primary contact physiotherapy-led vestibular clinic: A prospective blinded inter-rater agreement pilot study - Tamsin Smith; Jennifer Eakin; Christopher L. Payten; Fritha Noonan; Kelly Weir; Vicky Stewart (BMC, 2024)
Abstract Background Dizziness and vertigo are common referrals to Ear Nose Throat (ENT) outpatient services however these services have long waitlists for assessment. Primary contact physiotherapy-led vestibular clinics are recognized as improving access to care. This pilot study investigated agreement between physiotherapists and an ENT medical practitioner for diagnostic and management decisions in patients attending a primary contact physiotherapy-led vestibular clinic. Methods Prospective blinded inter-rater agreement study undertaken in an ENT primary contact physiotherapy-led vestibular clinic. Participants were adults referred to ENT from general practitioners, triaged (Category 2 or 3) to the primary contact physiotherapy-led vestibular clinic with clinical symptoms consistent with vestibular disorder. Primary outcome measures included agreement of diagnoses and management decisions made by an ENT medical practitioner and Physiotherapist based on a vestibular physiotherapy assessment. Adverse events were reviewed 11 months post data collection. Gwet's first order agreement co-efficient (AC1) calculated inter-rater reliability between physiotherapy and ENT. Results Fifty-one participants were recruited consecutively from the primary contact physiotherapy-led vestibular clinic. Physiotherapy and ENT had a substantial agreement (AC1 0.613) on diagnosis. AC1 between physiotherapy and ENT for recommending Magnetic resonance imaging (0.810) and computerized tomography (0.935) both indicated near perfect agreement. There was moderate to near-perfect agreement regarding management recommendations between physiotherapy and ENT. Substantial agreement (AC1 0.720) was found for recommendations for ENT input, near perfect agreement (AC1 0.933) for neurology input and moderate agreement (AC1 0.574) for physiotherapy input. There were no adverse events from physiotherapist's management decision, based on final recommendations undertaken 11-months post data collection. Conclusions Physiotherapists and ENT medical practitioner made comparable diagnostic and management decisions, based on physiotherapy and audiology hearing assessment, for adults with signs of vestibular dysfunction, within an ENT primary contact physiotherapy-led vestibular clinic. This study provides support for this type of Physiotherapy-led service in managing patients referred to an ENT service with vestibular dysfunction.